Pengaruh Eco-Efficiency, Sustainability Reporting, Dan Dividend Policy Terhadap Firm Value Yang Dimoderasi Profitability - Annisa Azka Rahmawati Aulia; Nera Marinda Machdar (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Rapid growth in the business world allows companies to showcase their advantages to attract public interest and invite investors to invest, but this actually gives rise to negative impacts such as social inequality. Therefore, companies are not only expected to pursue profits alone, but also to prioritize their responsibilities and the environment. The researcher's aim in writing this scientific article is to study and examine the influence of eco-efficiency, sustainability reporting and dividend policy on firm value moderated by profitability. This research is included in the category of qualitative descriptive research with literature study. The results of this research show that the variables eco-efficiency, sustainability reporting, and dividend policy have a positive effect on firm value. Furthermore, eco-efficiency, sustainability reporting, and dividend policy can be moderated by profitability on firm value.